Assessment of the awareness and performance of agricultural extension agents for their role in citrus marketing in Latakia Governorate - غانم, جالا; غسان يعقوب ,; غسان بدور, (Latakia University Journal -Biological Sciences Series, 2023)
The study was conducted to investigate the role of extension agents in citrus marketing as an influencing factor to increase farmers' income. Agricultural extension agents specialized in guiding farmers about citrus fruits in Latakia Governorate were selected through a questionnaire distributed to 40 agricultural engineers over extension offices. The study showed the positive impact of the agricultural extension agents attending training courses related to citrus marketing on their performance of their citrus marketing extension functions, and the lack of influence of the agricultural extension agents’ age, upbringing and experience in extension work on their performance of their citrus marketing extension role. Agricultural extension effectively provides productive extension services to citrus farmers in Latakia governorate, while there are shortcomings in the provision of marketing extension services for citrus, and therefore it is production extension and not marketing extension. Most of the problems that impede the activation of marketing extension from the point of view of agricultural extension agents are concentrated in the high cost of production, the lack of means of transportation necessary for work, the lack of incentives and low salaries, in addition to the involvement of engineers in administrative work.